VEGETATION AND SOIL BIODIVERSITY ASSESSMENT IN TEMPERATE FORESTS SURROUNDING THE KHAZAR NABI MARSHES, IRAN - Mohammad Parsa Rahimi Siagurabi; Ali Kialashaki; Easa Mataji Amirrud; Majid Eshagh Nimvari (Association of Indonesian Forestry and Environment Researchers and Technicians, 2026)
A thorough understanding of biodiversity is crucial for the sustainable management and conservation of forest ecosystems. This study investigates vegetation cover in conjunction with key environmental factors—including physiographic features, soil characteristics, and climatic conditions—in the Nimvar Forest of Nowshahr, Iran. Vegetation zoning was conducted in areas surrounding the Khazar Nabi Marshes based on the degree of homogeneity and heterogeneity among vegetation units. The primary objective of this research is to evaluate vegetation and soil biodiversity within the temperate forests adjacent to the marshes. Plant diversity was quantified using the Simpson and Shannon-Wiener indices, while species richness was assessed through the Margalef and Menhinick indices. The Berger-Parker and Pielou’s indices were also employed to evaluate species dominance and evenness. Results indicated that both species diversity and richness reached their highest levels in the eastern, northern, and northeastern parts of the study area. Statistically significant differences in species richness and evenness (p < 0.05) were observed among these regions. The predominant soil texture in areas surrounding the marsh was sandy clay loam (62.5%). Notable variation was found in clay content (p < 0.01), organic matter (p < 0.01), and soil pH (p < 0.05). Beech species were most abundant on the northern slopes, whereas the Gramineae family represented the most dominant plant group overall. These findings emphasize the marsh’s role in shaping local vegetation patterns and soil attributes, contributing to the development of a distinct microhabitat with unique microclimatic conditions.